As vozes do truco saltando do céu - Silva, Francisco Carlos Tavares da (2021)
This dissertation aims to describe and interpret the universe of the card game called truco paulista, from its realization at the game table. Its main pillar is the ethnographic field research and visits to bars where there is the practice of truco paulista, especially king’s bar, in the city of Salto do Céu-MT. The work aims to describe and interpret truco paulista from three perspectives: the first, highlights the rules of the game in dialogue with the sociabilities experienced by the players in king’s bar and in the participation of tournaments; the second analyzes the languages of truco paulista between the facial reading of the game’s signals, the body languages, the oral/verbal communication in the game and the meanings pointed out through the player’s voices; and the third, delves into the exercise of truco paulista at the table through everyday life, thus presenting the structural mechanics of truco paulista and the game stories according to the player’s voices. Special attention is given to categories such as play, game, sport, luck, bad luck, emotion, courage, bet, performance, bluff, sonorities, brotherhoods, sensibilities and masculinities. Under this prism, the investigation gains relevance by offering significant clues of the universe and the meanings that constitute the structuring dimensions of the game, allowing us to understand the daily life lived by people who play truco paulista, through networks of interactions built on brotherhoods, sonorities and masculine sensibilities in the exercise of leisure.